Control system design for EPTB - Tan, Sing Guan (2019)
Air Conditioning and Mechanical Ventilation (ACMV) equipment is used extensively around the world. It is being used for various purposes in many types of buildings around the world. In Singapore, due to its hot and humid climate, ACMV equipment is commonly used to provide thermal comfort. Previous research was mainly on the Indoor air quality (IAQ) and the negative ion air performance on passive thermosiphon beam (PTB). This is because thermal comfort is only one of the many factors that contribute to good IAQ. As a result, many suffered from sick building symptoms (SBS), due to their reliance on air conditioning systems. The previous research focused on the effects of the position of the generator as well as the fall duct length of the PTB system. For my part, the project goal is to design a control loop for the Enhanced Passive Thermosiphon Beam (EPTB) system. The objective of this system is to research various control loops to increase the response time of the system, thereby also increasing the efficiency of the system.